Molecularly Imprinted-Solid Phase Extraction for Multi-Residues Analysis of Sudan Dyes in Sausage - Qiao, Fengxia; Chen, Ping (Asian Journal of Chemistry, 2011)
A Sudan II molecularly imprinted polymer (MIP) was synthesized and used as the selective sorbent for solid phase extraction (SPE) of Sudan dye (I, II, III and IV) residues in sausage samples. It showed higher affinity to Sudan dyes and could selectively enrich them from sausage matrix. Under the optimized solid phase extraction condition, the extracts were sufficiently clean for further chromatographic analysis with no interferences from template leakage and sausage matrix. Good linearity were obtained from 0.03-10 μg/g with the correlation coefficients r2 ³ 0.9994. The recoveries of four Sudans in sausages at three spiked levels were in the range of 96.8-103 %.